Association between gallbladder disease and colorectal neoplasia: a meta-analysis - Geng, Wenbin; Ma, Kai; Jiang, Yizhou; Peng, Shiyu; Wang, Xiaoyong (Scientific reports, 2025)
Although studies are available on the impact of gallbladder disease on the risk of colorectal neoplasia (CRN), the results are still debatable. We conducted a meta-analysis to summarize the correlation between gallbladder diseases and CRN. Eligible studies up to June 2024 were screened and retrieved using PubMed and Web of Science as well as by performing a manual review of references. Subgroup analyses stratified by region, location, and pathology of CRN were performed. Subgroup analyses stratified by classification and size of gallbladder disease were also performed. The pooled odd ratios (ORs) with 95% confidence intervals (CIs) were calculated. Sensitivity analyses were also performed. Begg’s test was conducted to determine the publication bias. A total of twenty studies were included. The results showed that gallbladder disease significantly increased the risk of CRN (OR = 1.20, 95%CI, 1.11–1.29, P < 0.001). Subgroup analyses showed that subjects with gallstones (OR = 1.14, 95%CI, 1.05–1.25, P = 0.003) or gallbladder polyps (OR = 1.23, 95%CI, 1.15–1.31, P < 0.001) had a significantly higher risk of developing CRN. Asians (OR = 1.21, 95%CI, 1.11–1.31, P < 0.001) with gallstones were more likely to develop CRN. Patients with larger gallbladder polyps (≥ 0.5 cm) were at a greater risk of developing CRN (OR = 1.96, 95%CI, 1.41–2.73, P < 0.001). Gallbladder polyps and gallstones increase the risk of CRN. Therefore, colonoscopy should be performed in patients with gallbladder disease, especially in those of Asian descent, as well as in people with large gallbladder polyps.